Impact of distance learning on the university students’ academic performance and experiences - Olvido, Michelle Mae Jugasan; Sanchez, Joje Mar Perino; Alejandro, Isidro Max Veloso (Institute of Advanced Engineering and Science, 2024)
The COVID-19 pandemic has impacted the Asian educational sector, prompting countries to shift educational delivery to distance learning. With this, the researchers determined the impact of distance learning during the pandemic on students’ academic performance. Utilizing a mixed-methods design employing data mining and focus group discussions, pertinent student data (n=1,305) and qualitative responses (students, n=10; teachers, n=5) from a teacher education college in a state university in Central Visayas, Philippines, were obtained and analyzed through descriptive, correlational, and thematic analyses. The students had very good academic performances in general education, professional education, and specialization courses, and most of them had online capabilities, including gadgets and internet access. No significant relationships were observed between the student’s academic performance and their profiles and distance learning capacity. The distance learning experiences of students and teachers were themed as challenges in adoption, the reality of the digital divide, the journey of the self, the role of the community, and the learning process. In conclusion, students’ profiles and distance learning capacity are not determinants of academic performance, and their experiences reflect the sad reality of distance learning in the first stage of the pandemic.